2014
DOI: 10.4161/temp.29800
|View full text |Cite
|
Sign up to set email alerts
|

Heat acclimation and cross tolerance to hypoxia

Abstract: Recent research has suggested a potential for some of the physiological and cellular responses to heat acclimation to carry over to improved tolerance of the novel stresses of another environment. This cross-tolerance is evident in heat-acclimated animals that exhibit enhanced tolerance to either hypoxic or ischemic stress, and is primarily attributed to shared cellular stress response pathways. These pathways include Hypoxia-Inducible Factor-1 (HIF-1) and Heat Shock Proteins (HSP). Whether these shared cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 84 publications
2
35
0
Order By: Relevance
“…The trajectory of the CVA aligns with the acclimatization response that typically occurs during the first 14 days of altitude exposure (Ely, Lovering, Horowitz, & Minson, 2014). During this period, a process of biochemical and metabolic changes essential for adaptation to lower oxygen environments occurs (Ely et al, 2014). Although many of the metabolites contributing to alteration in the athlete's metabolome remain unidentified, our findings highlight two distinct adaptation patterns occurring in athletes exposed to moderate altitude.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The trajectory of the CVA aligns with the acclimatization response that typically occurs during the first 14 days of altitude exposure (Ely, Lovering, Horowitz, & Minson, 2014). During this period, a process of biochemical and metabolic changes essential for adaptation to lower oxygen environments occurs (Ely et al, 2014). Although many of the metabolites contributing to alteration in the athlete's metabolome remain unidentified, our findings highlight two distinct adaptation patterns occurring in athletes exposed to moderate altitude.…”
Section: Discussionsupporting
confidence: 68%
“…Importantly, changes in the plasma metabolites were observed at day 3, with a return to baseline levels by 14 days. The trajectory of the CVA aligns with the acclimatization response that typically occurs during the first 14 days of altitude exposure (Ely, Lovering, Horowitz, & Minson, 2014). During this period, a process of biochemical and metabolic changes essential for adaptation to lower oxygen environments occurs (Ely et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…This concept of cross-adaptation was initially proposed by Hessemer, Zeh and Bruck (1986), and more recently by Maloyan et al (2005); the former basing their suggestion on physiological responses at the systems level to cold and heat exposure, and the latter providing evidence of cross-adaptation at the cellular level. Many groups have attempted to provide support for the theory of cross-adaptation at the systems level (Ely, Lovering, Horowitz, & Minson, 2014;Lee, Miller, James, & Thake, 2016;White et al, 2016). We, too, have addressed this issue, and contrary to most of the reported studies, found sparse evidence of cross-adaptation (Sotiridis, Debevec, Ciuha, Eiken, & Mekjavic, 2019a;Sotiridis et al, 2018;Sotiridis, Miliotis, Ciuha, Koskolou, & Mekjavic, 2019b).…”
Section: Introductionmentioning
confidence: 78%
“…This approach can be used to increase the physiological stress without the need for large increases in external training load (23). Whilst studies have examined the performance benefits of independent heat (21,33) and hypoxic exposure (4,20), the combined effects of heat and hypoxia are not yet well understood (5,8). with training conducted at low-moderate altitude (i.e.…”
Section: Introductionmentioning
confidence: 99%